Análise de marcadores culturais em quarto de despejo e casa de alvenaria e as respectivas traduções, à luz dos estudos da tradução baseados em corpus - Capelett, Patrícia Cristina (2016)
In this study, we investigated the translation of cultural markers present in two works written by Carolina Maria de Jesus: Quarto de Despejo: diário de uma favela, translated by David St. Clair as Child of the Dark; and the other, Casa de Alvenaria: diário de uma ex-favelada, by Robert M. Levine and Arrington Jr. as I m going to a little house: the second diary of Carolina Maria de Jesus. We investigated features of explicitation and simplification found in the respective translated texts. We also analyzed how the vocabularies that represent Brazilian cultural aspects were translated in the respective target texts. For it, we adopted Camargo s interdisciplinary proposal (2005, 2007), based on Corpus-Based Translation Studies (Baker, 1993, 1995, 1996); Corpus Linguistics (Berber Sardinha, 2004, 2009), studies on cultural domains (Nida, 1945; Aubert, 1981), and on translation modalities (Aubert, 1998). For data generation we used the linguistic program WordSmith Tools, version 6.0, which enable us to analyse data in a more dynamic way. The results obtained suggest that David St. Clair s output shows patterns more likely to be consciously reproduced on the basis of the source text. On the other hand, Robert M. Levine and Arrington Jr seem to be closer to the normal patterning of translated English, because they used more strategies to adapt both language/cultural complexes.